Synthesis of poly(Rac-lactide) using Tri-n-butyltin(IV) n-butoxide as initiator: The investigation on stereochemistry and polymerization mechanism - Wanich Limwanich (2018)
© 2018, Chiang Mai University. All rights reserved. The ring-opening polymerization (ROP) of racemic-lactide (rac-LA) initiated by the synthesized tri-n-butyltin(IV) n-butoxide (nBu3SnOnBu) was investigated for first time by proton-and carbon-13 nuclear magnetic resonance spectroscopy (1H-and13C-NMR). The polymerization of rac-LA with nBu3SnOnBu and tin(II) octoate (Sn(Oct)2) was conducted under bulk condition. The synthesized nBu3SnOnBu showed high moisture-oxygen stability and solubility in the molten rac-LA. The13C-NMR spectra of poly(rac-LA) obtained from nBu3SnOnBu and Sn(Oct)2were slightly different indicating the different stereochemistry of synthesized polymers. The probabilities in forming of a new isotactic dyad (Pi) and the average block length of L-lactyl units (Li) in poly(rac-LA) obtained from nBu3SnOnBu was higher than Sn(Oct)2. From the results, the preferentially isotactic and heterotactic poly(rac-LA) were obtained from nBu3SnOnBu and Sn(Oct)2, respectively. The polymerization mechanism of rac-LA with the synthesized nBu3SnOnBu and Sn(Oct)2 initiating systems was proposed through the well-known coordination-insertion mechanism.